Synthesis and biological evaluation of piperazine derivatives as anthelmintic agents (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The purpose of this study is based upon synthesis of a series of 1,4-disubstituted piperazine derivatives through two step reaction. This protocol involves the formation of various acid chlorides (3a-3j) through reaction of substituted acid with thionyl chloride in the presence of a drop of dimethyl formamide as a catalyst. The second step involves the reaction of compounds (3a-3j) with methyl piperazine, affording target compounds (5a-5j).The structures of target compounds were elucidated from the data of the different spectral methods of analysis. In addition, a mass spectrum, for a representative example, was carried out where the expected fragmentation pattern is in accordance with the structure of the proposed compound. The anthelmintic activity of the synthesized derivatives (5a-5j) was investigated in vitro against Eisenia fetida. All the investigational compounds (5a-5j) exhibited promising anthelmintic activity at minimal dose of 5mg/ml in comparison with reference drug Piperazine citrate.